Occurrence of Deoxynivalenol, Nivalenol, and Their Glucosides in Korean Market Foods and Estimation of Their Population Exposure through Food Consumption - Sang Yoo Lee; So Young Woo; Fei Tian; Jeonghun Song; Herbert Michlmayr; Jung-Bok Kim; Hyang Sook Chun (Toxins, 2020)
Major type B trichothecene mycotoxins, including deoxynivalenol (DON), nivalenol (NIV), and their respective glucoside conjugates, deoxynivalenol-3-β-D-glucose (DON3G) and nivalenol-3-β-D-glucose (NIV3G), are present in food products, such as cereals, legumes, and their processed products. Thus, here, DON, NIV, and their 3-β-D-glucosides were monitored in 506 Korean market foods, and exposure to these mycotoxins was estimated in the population consuming these foods. The accuracy and precision of our method, which simultaneously determined four toxins, were 80.1−106.5% and 0.3−12.4%, in four representative food matrices assessed. The incidences of DON, DON3G, NIV, and NIV3G among all food samples tested were 13%, 8%, 12%, and 5%, respectively. The glucoside conjugate with free toxin was found to have the maximum co-occurrence of 49%. The estimated daily intakes of DON, DON3G, NIV, and NIV3G through food intake under four different scenarios were 0.019−0.102, 0.004−0.089, 0.007−0.094, and 0.002−0.095 μg kg−1 body weight (b.w.) day−1, respectively, which are lower than the established health-based guidance values. Overall, our results suggest that the estimated exposure of the Korean population to type B trichothecenes, namely, DON, NIV, and their 3-β-D-glucoside conjugates, may not pose a potential health risk.